Hybrid photonic crystal fiber for highly sensitive temperature measurement - Xu, Zhilin (2020)
A hybrid photonic crystal fiber (PCF) is proposed and demonstrated for highly sensitive temperature measurement. The hybrid PCF is formed by selectively infiltrating liquid crystal 5CB into the first ring of air holes around one silica core of a twin-core PCF (TCPCF). In the modified TCPCF, one silica core guides light with a total internal reflection (TIR) mechanism, while the other silica core guides light through a photonic bandgap (PBG) mechanism, due to the infiltration of high refractive index 5CB. The co-existing of TIR and PBG waveguiding mechanisms in the TCPCF leads to a hybrid light guiding mechanism PCF, i.e. hybrid PCF. Theoretical analysis reveals that the TIR-guided core mode, PBG-guided core modes and 5CB channel modes in the hybrid PCF can concurrently propagate and interfere with each other, which is further verified by experimental results. Besides, experimental investigation on the temperature response of the hybrid PCF shows that the temperature sensitivities can be up to 4.91 nm °C−1 for nematic phase of 5CB, and −3.68 nm °C−1 for isotropic phase of 5CB, respectively. The proposed hybrid PCF is promising for applications of temperature-tunable optical filtering in optical fiber communication, sensing and laser systems.